2012
DOI: 10.1016/j.ajpath.2012.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals that miR-155 Regulates the PI3K-AKT Pathway in Diffuse Large B-Cell Lymphoma

Abstract: The aberrant expression of microRNA-155 (miR-155), which has emerged as having a significant impact on the biological characteristics of lymphocytes, plays important roles in B-cell malignancies, such as diffuse large B-cell lymphoma (DLBCL). DLBCL is the most common non-Hodgkin's lymphoma in the adult population, accounting for approximately 40% of newly diagnosed non-Hodgkin's lymphoma cases globally. To determine the specific function of miR-155, a quantitative proteomics approach was applied to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 35 publications
9
92
1
3
Order By: Relevance
“…The PI3K/Akt pathway plays an important role in the regulation of TJ assembly and integrity (González-Mariscal et al, 2008). At the same time, Akt signaling is activated by overexpressed miR-155 and downregulated after miR-155 inhibition (Yamanaka et al, 2009;Huang et al, 2012). In agreement with these previous studies, Akt phosphorylation levels (both at Thr308 and Ser473) were Ͼ3-fold lower in the Inhibitor samples compared with Controls (Fig.…”
Section: Downregulation Of Mir-155 Results In Increased Expression Ofsupporting
confidence: 80%
See 1 more Smart Citation
“…The PI3K/Akt pathway plays an important role in the regulation of TJ assembly and integrity (González-Mariscal et al, 2008). At the same time, Akt signaling is activated by overexpressed miR-155 and downregulated after miR-155 inhibition (Yamanaka et al, 2009;Huang et al, 2012). In agreement with these previous studies, Akt phosphorylation levels (both at Thr308 and Ser473) were Ͼ3-fold lower in the Inhibitor samples compared with Controls (Fig.…”
Section: Downregulation Of Mir-155 Results In Increased Expression Ofsupporting
confidence: 80%
“…A negative regulation of ZO-1 expression by miR-155 has been demonstrated previously (Tian et al, 2013); however, its exact mechanism is unclear. Based on our analysis, we speculate that ZO-1 stability is mediated via a decrease of Akt activity and induced by miR-155 downregulation, which was also demonstrated by others (Yamanaka et al, 2009;Huang et al, 2012). Our results indicate that Akt phosphorylation could be induced by the upregulation of a direct miR-155 target protein, Rheb, which can supress Akt phosphorylation via an S6K-insulin receptor substrate protein-Akt feedback loop (Di et al, 2012;Cao et al, 2013).…”
Section: Discussionmentioning
confidence: 72%
“…One signaling pathway that is targeted at multiple levels by mir-155 (15,25,26), and could reasonably account for the defect observed, is the PI3K/Akt signaling cascade. We isolated CD8 + T cells from WT and 155KO mice and stimulated them with anti-CD3 for 30 min in vitro.…”
Section: Mir-155 Promotes T Cell Survival Via Aktmentioning
confidence: 99%
“…In addition, miR-155 suppresses the in vitro growth-inhibitory effects of TGF-β1 and BMP2/4 in DLBCL cells by SMAD5 downregulation, 59 and it controls PI3K-AKT pathway activity by PIK3R1 targeting. 60 Furthermore, overexpression of this miRNA promotes TNFα-dependent proliferation of DLBCL cells in vivo in xenotransplanted mice. 56 Recently, it has been demonstrated that SHIP1 is differentially expressed between the two molecular subtypes of DLBCL, GC B-cell-like, and activated B-cell-like (ABC) DLBCL.…”
Section: Aberrant Expression Of Mirnas In B-cell Lymphomas and Their mentioning
confidence: 99%